A Knitting Copolymerization Strategy to Build Porous Polytriazolium Salts for Removal of Anionic Dyes and MnO4−. Issue 15 (9th May 2022) - Ai, Chenxiang; Tang, Juntao; Zhang, Qingqing; Tang, Xincun; Wu, Shaofei; Pan, Chunyue; Yu, Guipeng; Yuan, Jiayin
Abstract: Although considerable efforts have been devoted to novel ionic porous networks (IPNs), the development of them in a scalable manner to tackle the issues in pollutant treatment by adsorption remains an imminent challenge. Herein, inspired by natural spider webs, a knitting copolymerization strategy is proposed to construct analogue triazolium salt‐based porous networks (IPN‐CSUs). It is not only convenient to incorporate the cationic motifs into the network, but easy to control over the contents of ionic pairs. The as‐prepared IPN‐CSUs displays a high surface area of 924 m 2 g −1, a large pore volume of 1.27 cm 3 g −1 and abundant ionic sites, thereby exhibiting fast adsorption rate and high adsorption capacity towards organic and inorganic pollutants. The kinetics and thermodynamics study reveal that the adsorption followed a pseudo‐second‐order kinetic model and Langmuir isotherm model correspondingly. Specifically, the maximum adsorption capacity of the IPN‐CSUs is as high as 1.82 mg mg − 1 for permanganate ions and up to 0.54 mg mg −1 for methyl orange, which stands out among the previously reported porous adsorbents so far. It is expected that the strategy reported herein can be extended to the development of other potential efficient adsorbents in water purifications. Abstract : Inspired by the fabrication of natural spider webs, a knitting copolymerization strategy is proposed to construct analogue triazolium salt‐based cationic porous organic polymers (IPN‐CSUs) for efficient removal of permanganate ions and methyl orange.